Factors affecting the distribution patterns of aquatic macrophytes - Dar Naseer Ahmad; Pandit Ashok Kumar; Ganai Bashir Ahmad (Limnological Review, 2014)
Aquatic macrophytes constitute important components of many freshwater ecosystems. The manifold role of aquatic macrophytes in freshwater habitats is closely linked to their distribution, which in turn depends on a myriad of factors. Foremost, among these are light, water temperature, water quality changes and nutrient enrichment, sediment composition and fluctuations in water levels. Light and temperature are of paramount importance in determining the distribution (with depth, season and latitude), thereby influencing productivity and species composition as well. Sediment compositions markedly affect the growth rates of macrophytes which in turn have a profound influence on the distribution of aquatic macrophytes. Water quality changes and nutrient enrichment can cause considerable variations in the species richness, composition, and density of aquatic vegetation. The reduction in water levels could bring drastic changes in the species composition and distribution of macrophytes. Factors associated with competition, herbivory, land use and land cover changes etc. also play an important role in shaping macrophyte distribution and community structure. In this review we examine both biotic and abiotic factors that influence the structural attributes like species composition, distribution, abundance and diversity of aquatic macrophytes.